Climate variability, Food (in)Security and Conflict on Hatiya Island - Suza, Ma (Wageningen University & Research, 2022)
Delivered during the UIU-WUR Knowledge Workshop on Climate and Food Security in Bangladesh, the presentation discussed the results of the focus group discussions in climate vulnerable areas and case studies on Fishermen-Coastaguard conflict.